Progress on Development and Rehabilitation Mechanism of Upper Extremity Lymphedema after Radical Mastectomy - Na XIE; Jie JIA (康复学报)
By reviewing the related literature at home and abroad, we summarized and analyzed the development and rehabilitation mechanism of upper limb lymphedema after radical mastectomy. The results showed that upper limb overload, trauma and infection were the most common causes of upper limb lymphedema, and surgical methods, postoperative radiotherapy and chemotherapy, tumor recurrence, obesity and so on were considered as related risk factors. The main pathophysiological mechanisms of upper limb lymphedema were the destruction of lymphatic vessels, the obstruction of lymphatic circulation, and the retention of extracellular fluid in the interstitial space. The retained fluid was very susceptible to infection due to the high protein content, and the repeated inflammatory stimulation further aggravated the process of edema. The rehabilitation mechanism included the compensation of drainage of contralateral side, the promotion of distal reflux and the regeneration of lymphatic vessels, so as to eliminate the swelling of upper limb.